Direct reduction of iron ore - Dalusong, Angelita A.; De Jesus, Emily C.; Salazar, Sonia; Ycasiano, Natividad (Diliman, Quezon City College of Engineering, 1971)
Capacity: 100 tons/day -- Total product cost: 9,175,578 -- Total product value: 21,000,000 -- Gross profit (before taxes): 11,824,422 -- Annual percentage return on fixed capital investment: 64% -- Pay-out time: 1.40 yrs. -- Break-even point: 15% of maximum capacity
Plant Design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Metallurgical plants; Steel-works.